2021
DOI: 10.1002/smll.202103632
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Sub‐Surface to Electrocatalytic Activity in Atomically Precise La0.7Sr0.3MnO3 Heterostructures

Abstract: the redox of these metals during cycling, such as in RuO 2 [14] and Ni-based oxides, [15] can be used to estimate their surface concentration. The density of active sites is often simply approximated by the exposed geometric surface area (measured by, e.g., microscopy or N 2 adsorption [16] ) or the electrochemical surface area (ECSA) by assumptions regarding intrinsic capacitance. [15,[17][18][19] However, all of these normalization approaches imply that electrochemical activity is governed exclusively by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…The high-quality of the epitaxial LSMO single layer (thickness of 28 nm) was confirmed by a separate growth (Figure S3). The main Bragg peak of the HZO thin film with t = 9.5 nm appeared at 2θ = 30.1°, closely aligning with the position of the O (or R) phase of HZO (111) reflection typically observed in polycrystalline films. , In polycrystalline films, the O(111) peak is generally observed at 2θ = 30.5°. This indicates that a lattice expansion of approximately 1.2% along the out-of-plane direction (larger d (111) spacing) occurred in the epitaxial thin film owing to the compressive strain.…”
Section: Resultssupporting
confidence: 70%
“…The high-quality of the epitaxial LSMO single layer (thickness of 28 nm) was confirmed by a separate growth (Figure S3). The main Bragg peak of the HZO thin film with t = 9.5 nm appeared at 2θ = 30.1°, closely aligning with the position of the O (or R) phase of HZO (111) reflection typically observed in polycrystalline films. , In polycrystalline films, the O(111) peak is generally observed at 2θ = 30.5°. This indicates that a lattice expansion of approximately 1.2% along the out-of-plane direction (larger d (111) spacing) occurred in the epitaxial thin film owing to the compressive strain.…”
Section: Resultssupporting
confidence: 70%
“…The extrinsic activity of an electrocatalyst is controlled by various factors, including the number of accessible active sites, electrical conductivity, and porous structure. , The surface morphology of the catalyst plays a critical role in influencing these factors, thereby determining the extrinsic activity. Nanostructuring and the formation of porous structures are two widely used strategies to engineer the catalyst surface morphology for enhancing the extrinsic activity.…”
Section: Design Strategies For Improving Catalytic Performancementioning
confidence: 99%
“…[207] The polar heterostructure can also be useful in chemical functionalities, such as electrocatalytic activity of which the studies on transition metal oxide thin films are ever more increasing. [208,209] Kim et al showed that the watersplitting performance of WO 3 could be significantly enhanced by the interfacial band offset from the atomically thin polar LAO layer. [210]…”
Section: Band Alignment (Modulation Doping)mentioning
confidence: 99%